2022
DOI: 10.1002/jmor.21479
|View full text |Cite
|
Sign up to set email alerts
|

Form and function in the avian pelvis

Abstract: The avian pelvis plays a critical role in the hindlimb function of birds, connecting the hindlimb and axial skeleton and serving as the major attachment site for proximal hindlimb musculature. To assess how diversification of locomotor modes in birds has impacted the evolution of avian pelvic morphology, we conducted a twodimensional geometric morphometric analysis of bird pelves in dorsal and lateral views from 163 species (n = 261) across Aves. We investigated the relationships among pelvic shape and ecology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…Moreover, these obtained osteometric data offer significant insights into crucial scientific fields, including evolutionary studies, developmental research and forensic sciences (Pitakarnnop et al, 2017;Yilmaz & Demircioglu, 2021). It is especially important to examine the morphometric and morphological features of the pelvis in birds, to determine the phylogenic and allometric characteristics of bird species, to reveal their locomotor behaviour, to determine their ecological diversity, to control the healthy laying of eggs and to evaluate various congenital or acquired pathological changes related to the pelvis region (Frank et al, 2022; Reddy & Sivajothi, 2018;Rosen, 2012;Shatkovska et al, 2018). In recent years, significant advancements in computer technologies have led to the utilization of various medical imaging techniques for examining the anatomical structures of exotic pet animals.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, these obtained osteometric data offer significant insights into crucial scientific fields, including evolutionary studies, developmental research and forensic sciences (Pitakarnnop et al, 2017;Yilmaz & Demircioglu, 2021). It is especially important to examine the morphometric and morphological features of the pelvis in birds, to determine the phylogenic and allometric characteristics of bird species, to reveal their locomotor behaviour, to determine their ecological diversity, to control the healthy laying of eggs and to evaluate various congenital or acquired pathological changes related to the pelvis region (Frank et al, 2022; Reddy & Sivajothi, 2018;Rosen, 2012;Shatkovska et al, 2018). In recent years, significant advancements in computer technologies have led to the utilization of various medical imaging techniques for examining the anatomical structures of exotic pet animals.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies have reported that the majority of measurement parameters obtained from the pelvis tend to be higher in males compared to females. However, the angle measurement parameters of the pelvis are generally found to be higher in females (Celimli et al., 2008 ; Monteiro et al., 2013 ; Pitakarnnop et al., 2017 ; Yilmaz et al., 2020 ). Consistent with the information provided, our study revealed that all linear measurement values ( L 1, L 2, L 3, L 4, L 5, L 6, L 7, L 8, L 9, L 10 and L 11) exhibited statistically significant differences between the sexes, with male budgerigars showing higher values compared to female budgerigars ( p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It would seem that the possibility of contact with the thorax is reduced. However, divers' thigh is short (Kurochkin, 1971;Raikow, 1985) and the pelvis is very narrow (Kurochkin, 1971;Raikow, 1985;Bogdanovich, 2003;Ibáñez & Tambussi, 2012;Frank et al, 2022). In addition, foot-propelled divers have elongated cnemial process on tibiotarsus (Raikow, 1985;Livezey & Humphrey, 1986;Hinić-Frlog & Motani, 2010), which is oriented cranially.…”
Section: Discussionmentioning
confidence: 99%